Usage of E- Resources in Law Libraries in India (LIS TODAY, 2023)
The significance of criminal training is gaining reputation day via way of means of day. A  library is an area wherein we gather the statistics from numerous reasserts both on line or offline.  Further that statistic is used to serve the want of the society without delay or indirectly. Objective of  regulation library is likewise the same. A powerful regulation library might suggest the provision of  the assets had to a criminal professional. In today’s dynamic international because of the  improvement of generation significance of criminal e- assets can’t be ignored. It could be very  beneficial for regulation students, academician for doing each day studies. The researcher in this text  will spotlight the significance of e- assets for regulation libraries. This paper may even attempt to  spotlight the alternative dimensions of criminal studies in addition to demanding situations  confronted via way of means of the librarian and different users.
Keywords: Legal; Information; Technology; E-Resources; Law Library